PENGARUH BERBAGAI FREKUENSI PEMBERIAN PAKAN PADA PEMBATASAN PAKAN TERHADAP PRODUKSI KARKAS AYAM BROILER - Imamudin, Imamudin; Atmomarsono, Umiyati; Nasution, Maulana Hamonangan (Animal Agriculture Journal, 2012)
The research was aims to determine the influence of various feeding frequencies on feed restriction towards broiler chickens on carcass production. The experiment used 200 days old chick broilers unsex. Feed diet were calculated 22,69% crude protein; 2930 kcal/kg metabolizable energy. Design used in this research was Completely Randomized Design (CRD), with 4 treatments and 5 replications, so there were 20 cages as experiment units. Each experiment unit consisted of 10 brid. T0: ad libitum feeding according to PT. Charoen Pokphand standard. T1: feeding with 75% standard feed which is given 4 times a day, T2: feeding with 75% of standard feed which is given 3 times a day, T3: feeding with 75% of standard feed which is given twice a day. The carcass weight of broiler chickens on T0: 1378,6 g, T1: 1292,4 g, T2: 1294,4 g dan T3: 1295,4 g. The carcass percentage of broiler chickens on T0: 71,86 , T1: 70,89 , T2: 71,19 dan T3: 72,37 %. The carcass percentage cut portion breast of broiler chickens on T0: 35,17, T1: 37,24, T2: 35,35 dan T3: 36,14 %. The carcass percentage cut portion drumstick of broiler chickens on T0: 6,52, T1: 6,68, T2: 6,48 dan T3: 6,59 %. The carcass percentage cut portion thigh of broiler chickens on T0: 8,12, T1: 8,35, T2: 8,14 dan T3: 8,11 %. The carcass percentage cut portion wing of broiler chickens on T0: 5,46, T1: 5,42, T2: 5,83 dan T3: 5,51 %. The carcass percentage cut portion back of broiler chickens on T0: 11,97, T1: 11,86, T2: 11,66 dan T3: 11,56 %. The results showed that the influence of feeding frequency and feed restriction no significant effect (P> 0.05) on weight carcass, carcass percentage and carcass cut portionKey words: feed restriction, carcass weight, carcass percentage and carcass cut portion, broiler chicken